2016
DOI: 10.1038/ncomms10980
|View full text |Cite
|
Sign up to set email alerts
|

Open-source image reconstruction of super-resolution structured illumination microscopy data in ImageJ

Abstract: Super-resolved structured illumination microscopy (SR-SIM) is an important tool for fluorescence microscopy. SR-SIM microscopes perform multiple image acquisitions with varying illumination patterns, and reconstruct them to a super-resolved image. In its most frequent, linear implementation, SR-SIM doubles the spatial resolution. The reconstruction is performed numerically on the acquired wide-field image data, and thus relies on a software implementation of specific SR-SIM image reconstruction algorithms. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
256
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 283 publications
(274 citation statements)
references
References 44 publications
0
256
0
1
Order By: Relevance
“…Thus, requiring intense tuning to achieve a proper reconstruction. As an example of this situation, we show in Supplementary Figure S7 an image reconstructed with our method and three reconstructions produced by an ImageJ/Fiji plug-in based on the tuning of a Wiener filter and an apodization function19. After several attempts to optimize the image we were not able to achieve a reconstruction of the quality provided by our method.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, requiring intense tuning to achieve a proper reconstruction. As an example of this situation, we show in Supplementary Figure S7 an image reconstructed with our method and three reconstructions produced by an ImageJ/Fiji plug-in based on the tuning of a Wiener filter and an apodization function19. After several attempts to optimize the image we were not able to achieve a reconstruction of the quality provided by our method.…”
Section: Discussionmentioning
confidence: 99%
“…In most of the publications, the structure of fenestrations in LSECs was described in fixed cells using electron microscopy, atomic force microscopy (AFM) or recently super‐resolution optical microscopy . However, in fixed (especially fixed‐dried) cells, the structure of fenestrations might be altered .…”
Section: Introductionmentioning
confidence: 99%
“…Last year our team reported that the quantitative imaging (QI) mode of atomic force microscopy (AFM) allowed the relatively fast and high‐resolution dynamic imaging of fenestrae in cultured LSECs . Moreover, high‐resolution three‐dimensional (3‐D) imaging of fenestrae on fixed LSECs using superresolution fluorescence microscopy recently became possible, indicating the future potential to investigate live LSECs under relevant physiological conditions . Those two Nobel Prize–awarded imaging technologies illustrate the impact of microscopy technology development on revealing new insights in LSEC biology and fenestrae.…”
mentioning
confidence: 99%